Pengaruh Kompensasi, Motivasi, Dan Disiplin Kerja Terhadap Kinerja Karyawan (Pada CV. Mitra Manshur) - Bashori, Mohamad Amirudin; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research was conducted to determine and analyze the influence of compensation, motivation and work discipline on the performance of CV employees. Mitra Mansur. The population in the study were CV employees. Mitra Mansur, totaling 42 employees. Meanwhile, the sampling technique used in this research is a saturated sample or census research and uses the SPSS analysis tool. The research results show that compensation, motivation and work discipline simultaneously influence employee performance and partially compensation, motivation and work discipline influence employee performance. Keywords: Compensation, Motivation, Work Discipline, Employee Performance